Analysis of Financial Performance Using the Allocation to Collection Ratio (ACR) and International Standard of Zakat Management (ISZM) Method - Faridatul Fajar, Siti; ‎ , Darna (KnE Social Sciences, 2024)
This study aims to analyze the level of effectiveness of zakat management organizations in distributing collected zakat funds and measuring the capacity and efficiency of national zakat management organizations in managing and distributing zakat funds through their programs. The analysis method uses the allocation to collection ratio (ACR) model and the International Standard of Zakat Management (ISZM). The data analyzed is the Annual Financial Report data and the financial performance report of the Badan Amil Zakat Nasional for the 2017-2021 period. The results of data analysis with ACR show that it must maintain its effectiveness and continue improving its financial performance. The results of the calculation of the efficiency level of the ISZM model can still improve efficiency in managing its fund expenditure and conducting its collection activities. The result of ISZM model capacity measurement, must maintain its potential, especially the distribution and collection of funds for Mustahiq empowerment programs. To increase the trust of zakat payers, this research acts as an input for national zakat management organizations to pay attention to their effectiveness and efficiency ratios using the ACR and ISZM methods. Assessment of organizational performance is important for management to evaluate performance in maintaining organizational sustainability and achieving the main objectives of the organization. Keywords: financial performance, allocation to collection ratio (ACR), International Standard of Zakat Management (ISZM)